Dominant Factors in the Behaviour of Mothers Performing Pregnancy Massage - Triana, Ani; Astika, Indah Novia (Ahmar Metastasis Health Journal, 2024)
Pregnancy massage is one of the complementary services during pregnancy that is attractive to pregnant women, but not many health workers provide this service. Currently, pregnant women are considering several factors related to pregnancy massage as an alternative service to overcome discomfort in pregnant women. The aim is to explain the dominant factors that influence mothers' behaviour in carrying out pregnancy massage. Quantitative research with cross-sectional design. 203 pregnant women were participating and were selected using purposive sampling techniques. Data collection was carried out in March-August 2023. Univariate and bivariate data analysis used the chi-square test and multivariate with the multiple logistic regression test. There were 163 people (80.3%) pregnant women who had good behaviour during pregnancy massage. Several variables that have a significant relationship are sources of information (p=0.023), knowledge (p=0.001), family support (p=0.001), and the role of health workers (p=0.001). Four variables that influence the behaviour of pregnant women are the role of health workers (POR=105.491), sources of information (POR=6.811), knowledge (POR=6.721) and family support (POR=5.836). It was concluded that the dominant factor in this research was the role of health workers.